Emptying your inbox : the 12 best practices for handling email - Stack, Laura (Productivity Pro, Inc., 2013)
Is your email your to-do list? Is it really keeping you organized? Technology CAN increase your productivity, if you use best practices for email. This eBook will guide you through the 12 Best Practices for Handling Email so that your inbox becomes your friend. Learning to control your email is fundamental to increasing your productivity. These skills will give you the foundation you need to keep your inbox under control.